Robotic versus laparoscopic revisional bariatric surgeries: a systematic review and meta-analysis - Karim Ataya; Hussein El Bourji; Ayman Bsat; Amir Al Ayoubi; Al Moutuz Al Jaafreh; George Abi Saad (Journal of Minimally Invasive Surgery)
Purpose: In recent years, the need for revisional bariatric surgery (RBS) procedures has experienced a noteworthy surge to confront complexities and weight recidivism. Despite being a subject of controversy for many, the utilization of the Da Vinci robotic platform (Intuitive Surgical, Inc.) may present benefits in RBS. This study aimed to evaluate the outcomes of robotic RBS in comparison to Laparoscopic RBS. Methods : A meticulous and thorough analysis was ensured through a comprehensive exploration of the literature, which included PubMed, Medline, Scopus, and Cochrane. This exploration was conducted in adherence to the directives outlined in the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The Newcastle-Ottawa scale was used for quality assessment. Results : A total of 11 studies were included in this meta-analysis, comprising 55,889 in the laparoscopic group and 5,809 in the robotic group. No significant differences were observed in the leak, bleeding, operative time, or length of stay across both groups. However, the robotic group showed higher rates of conversion to open surgery (odds ratio [OR], 0.65; 95% confidence interval [CI], 0.53-0.79; p < 0.0001; I2 = 0%), reoperation (OR, 0.70; 95% CI, 0.57-0.87; p = 0.0009; I2 = 6%), and readmission (higher rate of readmission in the robotic group; OR, 0.76; 95% CI, 0.62-0.92; p = 0.005; I2 = 30%) Conclusion : Robotic-assisted bariatric surgery has no significant advantage over conventional laparoscopic surgery. Further research is warranted to explore and evaluate surgeons’ methodology and proficiency differences.